Antioxidant capacity of Typha angustifolia extracts and two active flavonoids - Peidong Chen; Yudan Cao; Beihua Bao; Li Zhang; Anwei Ding (Taylor & Francis Group, 2017)
Context: The pollen of Typha angustifolia L. (Typhaceae) has been used as a traditional Chinese medicine for improving the microcirculation and promoting wound healing. Flavonoids are the main constituent in the plant, but little is known about the antioxidant activity of the principal constituent of the pollen in detail. Objectives: To assess the antioxidant activities of ethanol and water extracts and two constituents of the pollen. Materials and methods: Plant material (1 g) was extracted by 95% ethanol and water (10 mL × 2, 1 h each), respectively. The extracted activities (0.8-2.6 mg/mL) were measured by DPPH and the reducing activity of ferric chloride (1.7-2.6 mg/mL). Typhaneoside and isorhamnetin-3-O-neohesperidoside (I3ON) (2.8-70 μmol/L) were investigated on the relationship between NO, MDA and SOD in HUVECs treated with 100 μg/mL of LPS for 24 h. Results: Nine compounds were identified by UPLC-MS. Ethanol extract showed IC50 values in DPPH (39.51 ± 0.72) and Fe3+ reducing activity (82.76 ± 13.38), higher than the water extract (50.85 ± 0.74) and (106.33 ± 6.35), respectively. Typhaneoside and I3ON promoted cell proliferation at the respective concentration range of 2.8 to 70 μmol/L (p < 0.01). This two compounds decreased MDA (1.91 ± 0.10, 1.80 ± 0.34, p < 0.05) and NO levels (14.64 ± 0.08, 13.10 ± 0.88, p < 0.01), respectively, and increased SOD level (22.94 ± 2.48, 23.57 ± 2.38, p < 0.01) at the concentration of 70 μmol/L compared with LPS group. Conclusions: The constituents from Typha angustifolia could be a novel therapeutic strategy for LPS-induced inflammation.